Significance of Studying Literature: A Holistic Perspective - Humagain, Abhimanyu (International Research Journal of MMC, 2026)
The study explores the comprehensive value of literature in shaping intellectual, emotional, moral, and cultural understanding in human life. The objective of this study is to examine the multidimensional significance of studying literature from educational, psychological, and socio-cultural perspectives. The research employed an exploratory qualitative design to interpret and synthesize relevant theoretical insights. Secondary data were collected from scholarly books, journal articles, and online publications. The collected data were analyzed using a qualitative descriptive method. The sources of secondary data were published between 2020 and 2025 to ensure contemporary relevance. The findings from the comprehensive review of theoretical literature revealed twelve key findings highlighting the multifaceted significance of studying literature. These include the development of critical and analytical thinking, language and communication skills, empathy and emotional intelligence, cultural and historical preservation, creativity and imagination, moral and ethical reflection, personal growth and self-reflection, research and information literacy, literature as a medium of social commentary, lifelong learning and intellectual growth, its therapeutic power, and the exploration of new ideas. These findings reveal that literature serves as a vital instrument for holistic education and personal growth. This study benefits students, teachers, and researchers by deepening their understanding of literature’s transformative role in intellectual development and human flourishing.